Seasonality modulates habitat cover effects on avian cross-boundary responses and spillover - Larissa Boesing, Andrea; Bianchi, Felix J. J. A.; Rojas, Andrés; Polesso, Mariana; Kerches-Rogeri, Patrícia [UNESP]; César Ribeiro, Milton [UNESP]; Paul Metzger, Jean (Wiley, 2022)
Species cross-boundary response is a key mechanism affecting species spillover into agricultural fields. However, temporal changes in edge permeability, which may depend on the seasonal availability of resources in both matrix and native habitats, remain poorly understood. Here we tested how edge crossing behavior and the associated spillover of birds into sun coffee plantations respond to landscape structure and seasonality. We monitored the movement of six insectivorous understory bird species (four forest specialists and two forest generalists) using an automated telemetry system along a gradient of forest cover (7–60%) during two seasons (dry versus wet) at nine sampling sites at the Brazilian Atlantic forest. We monitored 116 individuals and obtained a total of 15 129 bird detections across seasons. Bird resistance to crossing edges was strongly driven by an interaction between seasonality and forest cover in the surrounding landscape, with higher resistance to crossing edges along the dry season and in landscapes with lower amount of forest cover. Furthermore, spillover patterns in plantations were driven by an interaction between forest cover and distance from forest edges, but this was most pronounced for forest-specialist bird species. Forest specialists moved more intensively and farther from edges in more forested landscapes, whereas forest generalists showed similar patterns of occupation regardless of forest cover and isolation. Our study contributes to a better understanding of avian cross-boundary responses and spillover in response to landscape structure across seasons, and the factors driving bird movement decisions in anthropogenic landscapes. There are a myriad of possible mechanisms governing movement decisions, and these mechanisms may interact in complex ways and remain important foci for research within the fields of tropical ecology and evolution.
Keywords: Atlantic forest; bird movement; birds; coffee plantations; habitat loss; landscape complementation